Crosstalk between gut microbiota and metastasis in colorectal cancer: implication of neutrophil extracellular traps - Wu, Jiawei; Dong, Wenyan; Pan, Yayun; Wang, Jingjing; Wu, Minliang; Yu, Yue (Frontiers in Immunology, 2023)
Primary colorectal cancer (CRC) often leads to liver metastasis, possibly due to the formation of pre-metastatic niche (PMN) in liver. Thus, unravelling the key modulator in metastasis is important for the development of clinical therapies. Gut microbiota dysregulation is a key event during CRC progression and metastasis. Numerous studies have elucidated the correlation between specific gut bacteria strains (e.g., pks + E. coli and Bacteroides fragilis) and CRC initiation, and gut bacteria translocation is commonly witnessed during CRC progression. Gut microbiota shapes tumor microenvironment (TME) through direct contact with immune cells or through its functional metabolites. However, how gut microbiota facilitates CRC metastasis remains controversial. Meanwhile, recent studies identify the dissemination of bacteria from gut lumen to liver, suggesting the role of gut microbiota in shaping tumor PMN. A pro-tumoral PMN is characterized by the infiltration of immunosuppressive cells and increased pro-inflammatory immune responses. Notably, neutrophils form web-like structures known as neutrophil extracellular traps (NETs) both in primary TME and metastatic sites, NETs are involved in cancer progression and metastasis.In this review, we focus on the role of gut microbiota in CRC progression and metastasis, highlight the multiple functions of different immune cell types in TME, especially neutrophils and NETs, discuss the possible mechanisms of gut microbiota in shaping PMN formation, and provide therapeutical indications in clinic.